(untitled) (Texas Journal of Medical Science, 2025)
The article discusses The frequency and timing of vulvar cancer (VC) recurrence depend on the stage of the disease and the depth of tumor invasion. The incidence of VC recurrence increases with increasing disease stage. Based on the timing of recurrence, it follows that the first 3 years after completion of treatment require particular vigilance for recurrence, which, according to our data, occurred in 73.19% of patients. Therefore, regular follow-up at least every 3 months is essential.